Upaya Pemulihan Pendapatan Nasional Sektor Pariwisata Melalui Kebijakan Fiskal di Indonesia Pasca Pandemi - Aisyah Alifiah Dinhaq Lubis; Dedek Kustiawati; Reka Fadlia Elvantio; Sri Sundari (Publikasi Indonesia, 2022)
The tourism sector is a contributor to state revenue in the form of foreign exchange and plays a role in increasing productivity and reducing unemployment. The existence of COVID-19 has greatly affected the balance of national income, which has decreased. The sectors most affected are transportation, travel, warehouses and the accommodation and food provision sector. Then the other sector is the tourism sector in Indonesia, about 11.83% of Indonesian workers are in the tourism industry sector. The purpose of this study is to review the impact of Covid -19 which has resulted in the decline of the tourism industry sector in Indonesia and also to respond to Government policies to handle the impact The existence of health quarantine policies, social distancing and Large-Scale Social Restrictions (PSBB) greatly affects the activities of the tourism and manufacturing sectors which causes economic growth to slow down so that national income declines. Tourism is one of the sectors most affected by the Covid-19 pandemic. The tourism sector is the mainstay sector of the national economy that has the potential to encourage economic growth in Indonesia. This is indicated by the increase in the development of foreign tourist arrivals, foreign exchange receipts from the tourism sector, and the contribution of the tourism sector to national GDP. Reduced labor force, unemployment and poverty will increase will cause state revenues in the form of income tax (PPh) to decrease, therefore there needs to be a strategy for economic recovery in the tourism sector, namely fiscal policy. Fiscal policy is one of the economic policies launched by a country to manage and direct the economy to a more conducive condition. The way that this economic policy is highlighted is by changing or updating the management of state revenues and expenditures. This study uses a qualitative descriptive method and the data for this research is based on library research in the form of books, literature, journals, articles about the tourism industry, and how to recover in the post-pandemic, namely fiscal policy. Data obtained through the Central Statistics Agency regarding the development of tourism before and after the pandemic.